THE CONTEXTUAL INTERPRETATION OF IRONY IN ENGLISH AND UZBEK LANGUAGES (Modern education and development, 2025)
The study compares and contrasts how irony is realized in English and Uzbek discourse, highlighting similarities and differences in their syntactic structures, lexical choices, and cultural references. While English tends to rely on direct, often individualistic expressions of irony such as sarcasm, Uzbek irony is more indirect, reflecting collectivist cultural values and an emphasis on politeness and social harmony. The paper also considers the role of context in determining whether an expression is perceived as ironic, with both languages relying heavily on contextual clues to communicate the intended meaning.